A systematic review and meta-analysis on early-childhood-caries global data - Anastasia Maklennan; R. Borg-Bartolo; R. J. Wierichs; M. Esteves-Oliveira; G. Campus (BMC, 2024)
Abstract Objectives The present study systematically reviewed and provided a meta-analysis on early childhood caries (ECC) global prevalence and its association with socioeconomic indicators, both geographical and regarding unemployment rate, national income as well as income inequalities. Methods Only cross-sectional or cohort studies covering ECC prevalence and experience in children younger than 71 months, reporting sample size, diagnostic criteria and conducted in urban and rural communities were considered. No language restriction was selected. Studies published from 2011 to 2022 available in PubMed, Web of Science, Embase and Open Grey literature were retrieved by ad hoc prepared search strings. The meta-analyses were conducted for both overall ECC prevalence and experience stratified by country of publication as well as measures of socioeconomic indicators using a random effects model using STATA 18®. Results One hundred publications reporting ECC data from 49 countries (published from 2011 to 2022) were included and summarized by meta-analysis. The lowest prevalence was reported in Japan (20.6%) and Greece (19.3%). The global estimated random-effect pooled prevalence of ECC was 49% (95%CI: 0.44-0.55). The random-effect pooled caries prevalence (ECC) was 34% (95%CI: 02.20-0.48) (Central/South America), 36% (95%CI: 0.25-0.47) (Europe), 42% (95%CI: 0.32-0.53) (Africa), 52% (95%CI: 0.45-0.60) (Asia-Oceania), 57% (95%CI: 0.36-0.77) (North America) and 72% (95%CI: 0.58-0.85) (Middle East). When stratified by gross national income (GNI) the ECC prevalence ranged from 30% ($20,000-$39,999) to 57% in countries with the lowest GNI (<$5000). Stratification by inequality index (Gini index) resulted in an ECC prevalence range of 39% (low inequality) to 62% (no inequality), while for life expectancy the ECC prevalence ranged from 28% in countries with the highest life expectancy (< 80 years) to 62% in countries with 71-75 years life expectancy. Discussion Within the limitations of this study (lack of certainty about the results as many countries are not represented and lack of uniformity in prevalence and experience data represented), results from 49 different countries reported a wide range of ECC prevalence. These reports indicated persisting high worldwide distribution of the disease. Both ECC prevalence and experience were associated with geographical areas and GNI. Registration PROSPERO: CRD-42,022,290,418.